Genetic Variability in Turmeric (Curcuma longa L.) - Dev, H.; Sharma, Vipin (International Journal of Bio-resource and Stress Management, 2022)
The investigation was carried out in the Department of Vegetable Science, Dr. YSPUHF, Nauni, Solan, HP, India during kharif May, 2011-January, 2012. The objective of the study was to assess the genetic variability of 40 diverse genotypes of turmeric collected from different parts of the country including 2 recommended varieties as checks viz.PalamLalima and PalamPitambar.This research work can be valued of immence importance over the time, as it may be of use for global breeders through exchange of germplasm in future.The observations were recorded on various growth, yield and quality parameters. High GCV and PCV were found for weight of mother and primary rhizomes, incidence of rhizome rot and curcumin content, indicating wide range of variations and offered better scope for improvement through clonal selection. High heritability coupled with high genetic gain were estimated for weight of mother and primary rhizomes and girth of primary rhizome, indicating that these characters were under additive gene effects and more reliable for effective clonal selection. High heritability coupled with moderate genetic gain for length and core diameter of mother, primary and secondary rhizomes, girth and weight of secondary rhizome and yield plant-1, plot-1 and hectare-1 were also observed, which indicated that clonal selection for these characters can also be effective. The overall assessment showed that there was wide variability among turmeric genotypes which has important implication for clonal selection of turmeric genotypes for yield and quality attributes.